Sosialisasi Undang-Undang Kepemilikan Tanah Adat Bagi Masyarakat Malamoi di Kelurahan Klablim - Rajab Lestaluhu; Reijeng Tabara; Mira Herawati Soekamto; Irnawati Irnawati (LP3M Universitas Muhammadiyah Sorong, 2023)
Indonesia, with various ethnic groups, has a wide area and diverse cultural diversity. With this wealth, the ownership of the territory or land of each ethnic group has different customary provisions. Along with the progress of time and an increase in population, it has caused many problems in customary land ownership. The Moi tribe in Klablin sub-district, Kota Sorong, has customary land ownership rights, but often experience disputes over their ownership. Therefore it is very necessary to socialize the law on customary land ownership for the Malamoi people in Klablim Village. This activity is carried out with the stages of observation, preparation and implementation of activities carried out with a lecture system and question and answer discussion. The results of this activity indicate that the problem with customary land ownership rights in Klablin Village by the Moi tribe does not have knowledge of ownership because it is owned by several clans, doubling or duplicating customary waiver letters, there is a sale above sale status and there is no registration of customary land in the eyes of government law . Settlement of customary land issues can be resolved by registering customary land ownership rights according to law and government regulations.